Non-invasive evaluation of cardiac repolarization in mice exposed to single-wall carbon nanotubes and ceria nanoparticles via intratracheal instillation. Issue 3 (15th April 2016) - Kosaraju, Karshak; Lancaster, Jarrett L.; Meier, Stephen R.; Crawford, Steven; Hurley, Steven; Aravamudhan, Shyam; Starobin, Joseph M.
Abstract : A novel method is proposed for non-invasive determination of cardiovascular toxicity due to ceria nanoparticles and single-wall carbon nanotubes from intratracheal instillation in mice. Abstract : We present results obtained from electrocardiogram (ECG) measurements performed on mice exposed to single-walled carbon nanotubes and ceria nanoparticles through instillation. From these non-invasive ECG measurements, QT and RR intervals were obtained at various times after exposure and used to compute a novel metric for evaluating cardiac signal propagation stability, the reserve of refractoriness (RoR). It is demonstrated that while the isolated QT and RR intervals are essentially uncorrelated with histological data from hematoxylin and eosin stains of control and exposed tissue samples, the RoR is sensitive to cardiovascular effects from the exposure to nanoparticles.